The conditioning of intervention effects on early adolescent alcohol use by maternal involvement and dopamine receptor D4 (DRD4) and serotonin transporter linked polymorphic region (5-HTTLPR) genetic variants. (2nd February 2015) - Cleveland, H. Harrington; Schlomer, Gabriel L.; Vandenbergh, David J.; Feinberg, Mark; Greenberg, Mark; Spoth, Richard; Redmond, Cleve; Shriver, Mark D.; Zaidi, Arslan A.; Hair, Kerry L.
Abstract: Data drawn from the in-home subsample of the PROSPER intervention dissemination trial were used to investigate the moderation of intervention effects on underage alcohol use by maternal involvement and candidate genes. The primary gene examined was dopamine receptor D4 ( DRD4 ). Variation in this gene and maternal involvement were hypothesized to moderate the influence of intervention status on alcohol use. The PROSPER data used were drawn from 28 communities randomly assigned to intervention or comparison conditions. Participating youth were assessed in five in-home interviews from sixth to ninth grades. A main effect of sixth-grade pretest maternal involvement on ninth-grade alcohol use was found. Neither intervention status nor DRD4 variation was unconditionally linked to ninth-grade drinking. However, moderation analyses revealed a significant three-way interaction among DRD4 status, maternal involvement, and intervention condition. Follow-up analyses revealed that prevention reduced drinking risk, but only for youth with at least one DRD4 seven-repeat allele who reported average or greater pretest levels of maternal involvement. To determine if this conditional pattern was limited to the DRD4 gene, we repeated analyses using the serotonin transporter linked polymorphic region site near the serotonin transporter gene. The results for this supplemental analysis revealed a significant three-way interaction similar but not identical to that found for DRD4 .